2008
DOI: 10.1097/tp.0b013e3181806c8c
|View full text |Cite
|
Sign up to set email alerts
|

Entecavir Therapy for Adefovir-Resistant Hepatitis B Virus Infection in Kidney and Liver Allograft Recipients

Abstract: The aim of our study was to assess the efficacy and safety of entecavir in kidney- and liver-transplant recipients with chronic hepatitis B virus (HBV) infection. Ten male transplant patients with chronic HBV infection (eight kidney- and two liver-transplant patients), who have become adefovir (n=9) or lamivudine-resistant (n=1) were given entecavir at 0.5 to 1 mg/d. All patients were HBs Ag positive: six were HBe Ag(-)/HBe Ab(+), and four were HBe Ag(+)/HBe Ab(-). After a median follow-up of 16.5 months, ente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 20 publications
1
42
0
2
Order By: Relevance
“…Other studies reported results with ETV in cohorts including both naïve and LAM-R patients, unfortunately with limited number of patient [42][43][44][45] .…”
Section: Ridruejo E Nuc Treatment In Rt Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies reported results with ETV in cohorts including both naïve and LAM-R patients, unfortunately with limited number of patient [42][43][44][45] .…”
Section: Ridruejo E Nuc Treatment In Rt Patientsmentioning
confidence: 99%
“…Treatment with ETV resulted in an appreciable drop in HBV DNA levels and a 50% HBV undetectability in both HBeAg positive and HBeAg negative patients after 16.5 mo of treatment without significant changes in glomerular filtration rate [42] . In our small experience we reported ETV use in 11 patients with several chronic renal diseases: 1 with stage 4 CKD, 7 in dialysis, and 3 RT recipients [43,44] .…”
Section: Ridruejo E Nuc Treatment In Rt Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the NUCs (LAM, adefovir and ETV) have been used in HBsAg + patients with chronic renal failure, on dialysis or after renal transplantation, in doses modified according to creatinine clearance [106][107][108]. Following renal transplantation, there are reports of worsening of renal graft function with adefovir; ETV may therefore be the drug of choice for this category of patients.…”
Section: Dialysis and Renal Transplant Patientsmentioning
confidence: 99%
“…Guidelines recommend prophylactic NA therapy during immunosuppressive-/chemotherapy for all patients who are HBsAg(+) [1][2][3]. There are limited data on the use of entecavir or tenofovir in this setting [38][39][40][41]; however, these agents are preferable to lamivudine because of the reduced risk of resistance development [1,3].…”
Section: Reactivation During Cytotoxic or Immunosuppressive Therapymentioning
confidence: 99%